Investigation on the Performance of Domestic Refrigerator with Zirconium Oxide-R134a Nanorefrigerant. (18th March 2022) - Baskaran, A.; Manikandan, N.; Tesfaye, JuleLeta; Nagaprasad, N.; Krishnaraj, R.
Abstract : This study investigates the performance of nanorefrigerants (R134a-ZrO2 ) in a domestic refrigerator at a concentration of 0.2 g/l without changing the components. Nanoparticles of ZrO2 of 0.2 g/L concentration with particle size 1-10 nm and 140 g of R134a have been charged, and investigations were carried out. Energy consumption and pull-down tests were conducted to investigate the performance of the refrigerator. The performance parameters like refrigeration capacity, compressor power, discharge temperature, coefficient of performance, and energy consumption were investigated for the nanorefrigerant (R134a-ZrO2 ), and the results were compared with base refrigerant R134a. The pull downtime, energy consumption, and discharge temperature are reduced with increased COP and compressor power when the system is operated with R134a-ZrO2 nanorefrigerant. Also, the thermophysical properties of the nanorefrigerant (R134a-ZrO2 ) are calculated and analyzed for the various volume fraction of nanoparticles.